A model of negotiation scenarios based on time, relevance andcontrol used to define advantageous positions in a negotiation - Rojas Altamirano, Omar Guillermo; López Hernández, Carlos (Mercados y Negocios, 2016)
Models that apply to negotiation are based on different perspectives that range from the relationship between the actors, game theory or the steps in a procedure. This research proposes a model of negotiation scenarios that considers three factors (time, relevance and control), which are displayed as the most important in a negotiation. These factors interact with each other and create different scenarios for each of the actors involved in a negotiation. The proposed model not only facilitates the creation of a negotiation strategy but also an ideal choice of effective tactics.